An empire on trial race, murder, and justice under British rule, 1870-1935 - Wiener, Martin J. (Cambridge University Press, 2009)
An Empire on Trial is the first book to explore the issue of interracial homicide in the British Empire during its height – examining these incidents and the prosecution of such cases in each of seven colonies scattered throughout the world. It uncovers and analyzes the tensions of empire that underlay British rule and delves into how the problem of maintaining a liberal empire manifested itself in the late nineteenth and early twentieth centuries. The work demonstrates the importance of the processes of criminal justice to the history of the empire and the advantage of a trans-territorial approach to understanding the complexities and nuances of its workings. An Empire on Trial is of interest to those concerned with race, empire, or criminal justice, and to historians of modern Britain or of colonial Australia, India, Kenya, or the Caribbean. Political and post-colonial theorists writing on liberalism and empire, or race and empire, will also find this book invaluable